Penerapan Metode Autoregressive Distributed Lag terhadap Faktor yang Mempengaruhi Harga Minyak Goreng Kemasan di Indonesia - Ratu Dinda Anggraeni; Nur Azizah Komara Rifai (Bandung Conference Series: Statistics, 2023)
Abstract. A set of ordered data at a certain time is called a time series. Time series analysis is divided into one variable (univariate) time series analysis and more than one variable (multivariate) time series analysis. Autorgeressive Distributed Lag (ARDL) is a multivariate time series analysis that is widely used in economics which applies a regression model with additional lag values ​​from the independent variables and lag values ​​from the dependent variable. This ARDL allows stationary variables at the level and at the first difference, making it easier for researchers to choose the method of analysis. Facts on the ground that there has been an increase in the price of cooking oil in Indonesia from October 2021 to March 2022 and there are factors predicting the cause are crude palm oil (CPO) production, export volume, and export value. The application of the ARDL method to factors affecting the price of packaged cooking oil in Indonesia was examined using monthly data from January 2017 to December 2020 sourced from the publication of the Central Bureau of Statistics of the Republic of Indonesia and the publication of the one data website of the Ministry of Commerce. The result show that the ARDL (2,3,3,1) model is good with an adjusted R-square value of 0.9617 which that the model can explain 96.17% of the variance in the price of packaged cooking oil in Indonesia. The ARDL models are: HRG MYKt = 3048 + 0,6155 HRG MYKt-1 +0,1712 HRG MYKt-2 + 0,00001960 PRODt+ 0,00007471 PRODt-1 - 0,00003302 PRODt-2 - 0,00008025 PRODt-3 + 0,0001933 VLM EKSt - 0,000803 VLM EKSt-1 - 0,0001292 VLM EKSt 2 + 0,0001822 VLM EKSt-3 - 0,0003799 HRG EKSt + 0,001843 HRG EKSt-1 + ut Abstrak. Sekumpulan data terurut pada rentang waktu tertentu disebut time series. Analisis time series terbagi menjadi analisis time series satu variabel (univariat) dan analisis time series lebih dari satu variabel (multivariat). Autorgeressive Distributed Lag (ARDL) merupakan salah satu analisis time series multivariat yang banyak digunakan dalam bidang ekonomi yang mana menerapkan model regresi dengan tambahan nilai lag dari variabel independen dan nilai lag dari variabel dependen. ARDL ini memperbolehkan variabel stasioner pada tingkat level dan pada first difference sehingga memudahkan peneliti dalam pemilihan metode analisis. Fakta di lapangan terjadi peningkatan harga minyak goreng di Indonesia sejak Oktober 2021 hingga Maret 2022 dan terdapat faktor prediksi penyebabnya adalah produksi minyak sawit mentah (CPO), volume ekspor, dan nilai ekspor. Penerapan metode ARDL terhadap faktor yang mempengaruhi harga minyak goreng kemasan di Indonesia diteliti menggunakan data bulanan pada Januari 2017 hingga Desember 2020 yang bersumber dari publikasi Badan Pusat Statistik Republik Indonesia dan publikasi website satu data Kementerian Perdagangan. Hasil penelitian menujukkan model ARDL (2,3,3,1) yang baik dengan nilai adjusted R-square 0,9617 yang berarti model dapat menjelaskan 96,17% varians harga minyak goreng kemasan di Indonesia. Model ARDL tersebut yaitu: HRG MYKt = 3048 + 0,6155 HRG MYKt-1 +0,1712 HRG MYKt-2 + 0,00001960 PRODt+ 0,00007471 PRODt-1 - 0,00003302 PRODt-2 - 0,00008025 PRODt-3 + 0,0001933 VLM EKSt - 0,000803 VLM EKSt-1 - 0,0001292 VLM EKSt 2 + 0,0001822 VLM EKSt-3 - 0,0003799 HRG EKSt + 0,001843 HRG EKSt-1 + ut